Pengaruh Variasi Putaran mesin, Komposisi Campuran Bioetanol Dan Tipe Vacuum Tube Terhadap Komsumsi Bahan Bakar Dan Komposisi Gas Buang Pada Motor Bakar Bensin Empat Langkah Satu Silinder - Agus Setiawan; Romy Romy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Experimental study on the installation of a vacuum tube in intake manifold has been done by observation at the effect of variations engine rotation and composition of bioethanol mixture with regard to fuel consumption and exhaust gas composition. This study used fuel E20, E30 and E40, the type of vacuum tube 4Y2 and Posh. Tests carried out on variations of the engine rotation 3000, 3500, 4000, 4500 and 5000 rpm. As result fuel consumption tends to increase as increasing engine rotation, it is more efficient with increasing ethanol in the fuel mixture and use a vacuum tube, the most efficient happened on fuel E40 with the installation of a vacuum tube type Posh in engine rotation 3000 rpm with consumption 0,21 L/hour. CO exhaust gas tends to decrease with increasing engine rotation, the ethanol in the fuel mixture with the installation of a vacuum tube, the lowest occurred on fuel E40 with installation a vacuum tube type Posh in engine rotation 5000 rpm with emission 0,06 %. CO2 tends to increase with increasing engine rotation, the ethanol in the fuel mixture and the installation of a vacuum tube, the highest on fuel E40 with a vacuum tube type Posh in engine rotation 5000 rpm with emission 13,60 %. HC tends to decrease with increasing engine rotation, the ethanol in the fuel mixture and the installation of a vacuum tube, the lowest occurred on fuel E40 with a vacuum tube type Posh in engine rotation 5000 rpm with emission 90 ppm.Keywords: Bioethanol, Exhaust Gas, Vacuum Tube